Conversational Assistant with Large Language Model Agent for Natural Interaction in Home Automation Environments - Yauri, Ricardo; Espino, Rafael (IAES Indonesian Section, 2025)
Digital transformation has driven the development of smart home automation systems for healthcare and remote assistance, which can integrate large language models, foundational models, and Retrieval-Augmented Generation techniques to design conversational assistants accessible to people with reduced mobility. In these cases, it is necessary to overcome usability barriers to control home devices because traditional home automation interfaces are not adapted to their specific needs. Previous research has identified systems such as voice control, gestures, and conversational agents based on generative artificial intelligence to facilitate assisted interaction in the home through home automation systems. This article describes a conversational agent, aimed at people with reduced mobility, to facilitate natural interaction with home automation environments, using technologies such as OpenAI, Langchain, and LlamaIndex. The results demonstrate the successful deployment of a web-based telecare platform based on conversational agents capable of retrieving technical documents through embedding, generating SQL queries, and MQTT topics for integration into real-world monitoring and assistance environments for people with reduced mobility.